The life cycle of Dermacentor nuttalli from the Qinghai-Tibetan Plateau under laboratory conditions and detection of spotted fever group Rickettsia spp. - Ma, Hejia; Ai, Jingkai; Kang, Ming; Li, Jixu; Sun, Yali (Frontiers in Veterinary Science, 2023)
Dermacentor nuttalli has been a focus of study because tick-borne pathogens have been widely identified in this tick from northern and southwestern China. The aim of this study was to characterize the life cycle of D. nuttalli under laboratory conditions and to detect spotted fever group (SFG) Rickettsia in the midgut and salivary glands of both field-collected and first laboratory generation adults. D. nuttalli ticks were collected in the field on the Qinghai-Tibetan Plateau from March to April 2021 and their life cycle was studied under laboratory conditions. Tick identify was molecularly confirmed, and SFG Rickettsia were detected in the midgut and salivary glands of males and females by PCR targeting different rickettsial genes. The results showed that the life cycle of D. nuttalli under laboratory conditions was completed in an average of 86.1 days. High positivity of Rickettsia spp. was detected in the midgut and salivary glands of both males (92.0%) and females (93.0%) of field-collected D. nuttalli ticks. However, a relatively lower positivity (4.0-6.0%) was detected in first laboratory generation adults. Furthermore, sequencing analysis showed that the Rickettsia sequences obtained in this study shared 98.6 to 100% nucleotide identity with Rickettsia slovaca and Rickettsia raoultii isolated from Dermacentor spp. in China. Phylogenetic analysis of Rickettsia spp. based on the gltA, ompA, ompB and sca4 genes revealed that the Rickettsia sequences obtained could be classified as belonging to R. slovaca and R. raoultii clades. This study described for the first time the life cycle of D. nuttalli from the Qinghai-Tibetan Plateau under laboratory conditions. Two species of SFG Rickettsia were detected in the midgut and salivary glands of males and females in both field-collected and first laboratory-generation adults of D. nuttalli. Our study provides new insights into pathogen detection in ticks in the Qinghai-Tibet Plateau, and the relationships among hosts, ticks, and pathogens.